2016
DOI: 10.1111/den.12598
|View full text |Cite
|
Sign up to set email alerts
|

Management of colorectal T1 carcinoma treated by endoscopic resection from the Western perspective

Abstract: Detection of early colorectal cancer is expected to rise in light of national colorectal cancer screening programs. This The present review article delineates current endoscopic risk assessments, differentiating invasive from non-invasive neoplasia, for high likelihood of lymph node metastasis in early colorectal cancer, also termed high-risk early colorectal cancer, and endoscopic and surgical resection methods from a Western hemisphere perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 149 publications
0
28
0
Order By: Relevance
“…Therefore, our results are in line with those of Schmidt et al [5], who also demonstrated a statistically significant difference in R0 resection rate between lesions ≤20 mm and lesions >20 mm. As already reported in previous studies, ESD represents the most reasonable endoscopic approach for rectal lesions >30 mm, especially for early adenocarcinomas, since EMR leads to piecemeal excision with an increased risk of incomplete resection [15][16][17][18][19][20][21]. Nonetheless, ESD for colonic lesions >30 mm might be technically demanding or even not feasible.…”
Section: Discussionmentioning
confidence: 76%
“…Therefore, our results are in line with those of Schmidt et al [5], who also demonstrated a statistically significant difference in R0 resection rate between lesions ≤20 mm and lesions >20 mm. As already reported in previous studies, ESD represents the most reasonable endoscopic approach for rectal lesions >30 mm, especially for early adenocarcinomas, since EMR leads to piecemeal excision with an increased risk of incomplete resection [15][16][17][18][19][20][21]. Nonetheless, ESD for colonic lesions >30 mm might be technically demanding or even not feasible.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, piecemeal resection is the critical risk factor for local recurrence, regardless of the ER method used [ 1 ]. National Comprehensive Cancer Network (NCCN) guidelines recommend follow-up for T1-stage CRC following ER in a single specimen ( en bloc ), negative vertical and lateral resection margins, histological grade 1 or 2, and without lymphatic and vascular invasion [ 13 ]. Submucosal invasion ≥1000 μm, presence of lymphovascular infiltration, poor differentiation, tumor budding, and incomplete resection are independently associated with increased risk of LNM and residual cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ESD is technically difficult, especially in fibrotic tissue due to previous excisions, it is time-consuming, and requires a prolonged learning curve for inexperienced endoscopists 24 . In fact, ESD outcomes from Western studies are substantially worse compared with Eastern studies, thereby limiting generalizability of the results 20 . However, ESD represents the only reasonable endoscopic approach for superficial (sm1) T1-ERC with a diameter exceeding 30 mm (i. e. large non-pedunculated colorectal polyps), since the use of the FTRD would not be feasible for technical reasons (cap diameter/length 13 /23 mm) 6 7 8 , while EMR often leads to piecemeal resection, challenging histopathological assessment of R0 resection, and increased risk of incomplete excision 24 .…”
Section: Discussionmentioning
confidence: 95%
“…As compared to established surgical curative treatments for rectal cancer (i. e. lower anterior resection with total mesorectal excision and abdominoperineal resection), less invasive trans-anal full-thickness excision techniques (e. g., conventional trans-anal excision, trans-anal endoscopic microsurgery (TEM), or trans-anal minimally invasive surgery (TAMIS)) have comparable 5- and 10-year survival rates 18 19 but clear advantages in limiting either surgery-related mortality or morbidity, and the need for a permanent stoma 19 . However, by reducing both the resected specimens and the mesorectal lymph node assessment, these treatments hamper the exact disease staging, thereby implying an increased risk of local recurrence and missed micrometastasis 20 . In addition, following either TEM or TAMIS, major complications have been reported in 1.5 – 7 % of patients and conversion to laparotomy with or without total mesorectal excision or temporary stoma is sometimes necessary 21 22 23 .…”
Section: Discussionmentioning
confidence: 99%